Improving the settleability of a metal sulphide suspension by the application of a magnetic field - Gqebe, Sibongiseni Yamkela (Department of Chemical Engineering, 2016)
Gravitational sedimentation of suspensions in various precipitation processes is hindered by colloidal stability. More especially in sulphide precipitation, where high levels of supersaturation dominate and nucleation is favoured. This results in a large number of colloidal particles with a highly negative surface charge, which remain suspended in solution. The high surface charge of the suspension results in strong attraction/interaction between the ions on the particle surface and counter-ions in solution. Moreover, this strong interaction between ions on the particle surface and counter-ions in solution results in a charge build-up that renders the suspension stable. In order to induce gravitational sedimentation of these particles, a redistribution of ions close to the particle surface is required. This study therefore seeks to redistribute ions close to the particle surface by applying a magnetic field. This results in the reduction of inter-particle electrostatic repulsive forces and subsequent increase in the zeta potential of a suspension. For the purposes of this study, a copper sulphide suspension was used. A T-mixer was used as the reaction zone for the precipitation of each suspension. Subsequent to this, the suspended copper sulphide particles were exposed to a range of field strengths for set exposure times and their zeta potential was measured before and after exposure to the magnetic field. The effect of magnetic field strength, exposure time and particle speed on the zeta potential were tested. All particles had an initial zeta potential value equal to or less than - 40 mV prior to magnetic field exposure. A significant increase in zeta potential was observed with values reaching a maximum of - 16.5 mV when exposed to a 2 T field strength for 40 minutes. An increase in the zeta potential corresponds to a reduction in repulsive electrostatic forces between suspended particles due to the Lorentz force exerted by a magnetic field on the particle surface. DLVO plots were used to quantify this reduction in repulsive electrostatic forces.